Assessing the impact the 'Mais Médicos' program on basic health care indicators - Mazetto, Débora (2018)
The 'Mais Médicos' Program was launched by the federal government in 2013 with the main objective of reducing the shortage of physicians in regions of socioeconomic vulnerability in Brazil. Since then, the program has been attracting interest in evaluating its effectiveness on the localities adhered. This paper aims to measure the effects generated by the 'Mais Médicos' Program on health indicators of Brazilian municipalities from an econometric approach of policy evaluation. Using a difference-in-differences methodology, the effects on indicators of basic health care, morbidity and mortality were analyzed from the Program data between 2013 and 2015. There are evidences that the 'Mais Médicos' Program has positive effects on the primary healthcare indicators, particularly on appointments, consultations, referrals, examinations, and home visits, and negative effects over some indicators of morbidity. However, the Program does not seem to have been able to reduce mortality in the municipalities.